Odpowiedź :
Cześć!
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
[tex]\frac{3}{7}+\frac{2}{7} =\boxed{\frac{5}{7} }[/tex]
b)
[tex]1\frac{2}{5}+2\frac{1}{5} =(1+2)+(\frac{2}{5} +\frac{1}{5}) =\frac{18}{5} =\boxed {3\frac{3}{5} }[/tex]
c)
[tex]4\frac{5}{8} +3\frac{1}{8} =(4+3)+\frac{5}{8}+ \frac{1}{8} =7+\frac{3}{4}=\boxed{7\frac{3}{4} }[/tex]
d)
[tex]3\frac{3}{4} -\frac{1}{4} =\frac{15}{4} -\frac{1}{4} =\frac{7}{2}= \boxed{3\frac{1}{2} }[/tex]
e)
[tex]\frac{5}{8}-8\frac{3}{8} = (12-8)+\frac{5}{8}-\frac{3}{8} =4+\frac{1}{4} =\boxed{4\frac{1}{4} }[/tex]
f)
[tex]6\frac{7}{10}-2 \frac{4}{10} =(6-2)+(\frac{7}{10} -\frac{4}{10})=4+\frac{3}{10} =\boxed{4\frac{3}{10} }[/tex]
g)
[tex]\frac{3}{8} \cdot\frac{2}{3} =\boxed{\frac{1}{4} }[/tex]
h)
[tex]\frac{4}{5}\cdot \frac{1}{2}= \boxed{\frac{2}{5} }[/tex]
i)
[tex]\frac{6}{7} \cdot \frac{1}{3} =\boxed{\frac{2}{7} }[/tex]
j)
[tex]\frac{3}{4} :\frac{2}{5} =\frac{3}{4}\cdot \frac{5}{2} =\frac{15}{8}=\boxed{1\frac{7}{8} }[/tex]
k)
[tex]\frac{3}{7} :\frac{1}{4} =\frac{7}{3} \cdot 4= \boxed{\frac{28}{4} }[/tex]
l)
[tex]\frac{3}{8}: \frac{2}{3} =\frac{3}{8} \cdot\frac{3}{2} =\boxed{\frac{9}{16} }[/tex]
Pozdrawiam,
MrBarte!